Experimental Investigation of Motion and Wave Induced Forced on Semi-Submersible in Regular Wave - Khairuddin, N.M.; Pauzi, Mohamad (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
For the design of safe and economic offshore structure the knowledge of the wave environment and related wave-structure interactions is required. In general, frequency domain analysis has been regarded as an adequate tool for the assessment of motion and loads which are needed to derive the stress and hydrodynamics forces as well as operational limitations. For investigating the behavior of response to specific sea conditions, this research analyzes the behavior of the response due to motion and wave forces as well as hydrodynamics with focus on a type square column. The frequency domain investigation has used to provide the response behaviors on the wetted body of the semi-submersible in regular waves. For investigation,, the selected sea condition for regular wave is generated in a physical wave tank, and the behavior of the response on the semi-submersible is evaluated at model scale. Equation of motion was formulated to evaluate the added mass, dampi ng and stiffness at every frequency step. In frequency domain analysis, the hydrodynamics responses were obtained.